Pemahaman Gaya Belajar pada Anak Usia Dini (THUFULA, 2013)
Learning style is a characteristic cognitive, affective and psychomotorbehavior, which acts as an indicator of relative stability for the learners feelinginterconnected and reacting to the learning environment. Learning style refersto the preferred way of learning learners. Generally, it is considered that aperson’s learning style is derived from personality variables, including cognitiveand psychological composition of the socio-cultural background, education andexperience. Diversity of learning styles of students need to firstly consider anyinstitution that they will join in. Almost all students (kindergarten) has a mixof learning styles, very few children who have only one learning style. Learningstyle is a mix of learning styles which children sometimes type at once visual andauditory or kinesthetic as well, or just a kinesthetic and visual.